CLASSROOM INTERACTION PATTERNS IN EFL CLASSROOM AT JAKARTA INTENSIVE LEARNING CENTRE (JILC) - Lisanty AD Indira Fibri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
This study aims at revealing what are the interaction patterns, interaction exchanges, and impacts of interaction in EFL Classroom. The samples of this study are the teacher and students of junior high school in one of the courses in Makassar, namely Jakarta Intensive Learning Centre (JILC). The approach employed in this study is qualitative approach. The type of this study belongs to discourse analysis (DA). Data collection of this study was conducted through (1) recording, (2) observation, and (3) interview. The study findings shows that the used of teacher students pattern as the dominant pattern that the teacher applied. The knowledge exchange is the dominant exchange that the teacher applied in classroom, it depends on the material that the teacher transferred for her students. The study finding shows the positive impacts from interaction that the teacher applied in EFL Classroom.